Can We Evaluate Hiatal Ballooning by Measuring the Anteroposterior Diameter With 2‐Dimensional Translabial Ultrasonography?. (13th October 2017) - Wen, Lieming; Zhou, Qichang
Abstract : Objectives: To analyze the association between the anteroposterior hiatal diameter and pelvic organ prolapse and to determine whether 2‐dimensional translabial ultrasonography can evaluate hiatal ballooning by measuring the anteroposterior diameter. Methods: This study was a retrospective analysis of 312 women seen for lower urinary tract symptoms or pelvic organ prolapse between December 2014 and July 2016. All women had an International Continence Society (ICS) Pelvic Organ Prolapse Quantification (POP‐Q) system examination and 4‐dimensional translabial ultrasonography. The anteroposterior hiatal diameter was measured in the midsagittal plane, and the hiatal area was measured in the minimal axial plane during the maximal Valsalva maneuver. Results: Valid data from 294 patients were analyzed. International Continence Society POP‐Q stage 0 was found in 121 women, stage 1 in 49, stage 2 in 78, stage 3 in 42, and stage 4 in 4. The anteroposterior diameter had an excellent linear correlation ( r  = 0.814; P  < .001) with the hiatal area during the Valsalva maneuver and was strongly related to ICS POP‐Q stages ( P  < .01). A receiver operating characteristic curve analysis proposed a cutoff of 6.0 cm for the anteroposterior diameter against ICS POP‐Q stage 2 and higher (sensitivity, 73%; specificity, 52%) and prolapse symptoms (sensitivity, 74%; specificity, 64%). Conclusions: The anteroposterior hiatal diameter, which represents hiatal distensibility in the midsagittal plane, can be used to evaluate hiatal ballooning. "Mild" ballooning was defined as an anteroposterior diameter measurement of 6.0 to less than 6.5 cm, "moderate" ballooning as 6.5 to less than 7.0 cm, and "marked" ballooning as 7.0 cm or greater.